PENGARUH JENIS DAN DOSIS PUPUK TERHADAP PERTUMBUHAN DAN HASIL JAGUNG MANIS DI LAHAN GAMBUT - Juharni Juharni; Joko Purnomo; Dewi Erika Adriani; Yudhi Ahmad Nazari (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2026)
The objective of the study is to assess the impact of various fertilizer combinations, in terms of kind and amount, on peatland sweet corn growth and yield. This study employed a factorial Randomized Complete Design. The design has three factors: the dose of chicken manure, biofertilizer dosage, and NPK fertilizer. Data analysis was performed using analysis of variance with a 5% DMRT follow-up test. Plant height, number of leaves, and wet and dry stover weight were among the observed parameters. The study indicated that the single factor of chicken manure and NPK fertilizer treatment had a significantly different effect on all of the parameters. The chicken manure treatment showed the highest yield, at 3 ton/ha, in both wet and dry stover weight parameters. NPK fertilizer treatment obtained a dose 300 kg/hadose. Biofertilizer only effected to plant height and the combination of chicken manure with biofertilizer only effected to the number of leaves.